The Influence of Service Quality and Customer Relationship Management with Satisfaction Intervening Variables on The Loyalty of Health Facilities I - M. Much Harry Syaeful; Rhian Indradewa (Quantitative Economics and Management Studies, 2022)
Patient loyalty is indicated by satisfaction a factor that can reflect the quality of service from the local health service. Customer Relationship Management is the management of its customers that can provide. This study aims to see the effect of Service Quality, Customer Relationship Management, Satisfaction, and patient loyalty. The population of this study focused on patients in health facilities in the Jasinga District by sampling, namely purposive sample where the sample was patients who used health facilities in Jasinga District as many as 205 respondents. This type of research is quantitative, with data collection by distributing questionnaires. The analytical method used is the Structural Equation Model (SEM-PLS) with the SMART PLS software program. Some of the findings in this study are that service quality has a positive effect on patient satisfaction. Customer Relationship Management has a positive effect on patient satisfaction. Customer Relationship Management has a positive effect on Patient Loyalty. Service quality has a positive effect on patient loyalty and finally, satisfaction has a positive effect on patient loyalty. This study has implications for increasing patient loyalty by providing information to help manage the quality of health services and customer relationship management by encouraging satisfaction so that it will always increase patient loyalty significantly.